2013
DOI: 10.1002/anie.201303457
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation of a Borohydride: Synthesis of a Carbene‐Stabilized Boryl Anion

Abstract: An acidic hydride! Thanks to the presence of a π-acceptor cyclic (alkyl)(amino)carbene (CAAC) and of two electron-withdrawing nitrile groups, a borohydride reacts with a base to give a carbenestabilized boryl anion, which reacts with carbon and metal electrophiles at the boron center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
104
0
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 56 publications
(25 reference statements)
4
104
0
18
Order By: Relevance
“…The favorable 3 : 3 stoichiometric relation of suitable functions in Cy 3 PBH 2 SiMe 3 on the one hand, and in reagents of the type [(LAu) 3 O] + on the other hand, appeared to offer the right conditions for the envisaged metathesis. It should be noted that similar effects have now been demonstrated for carbene-boranes [1].…”
Section: Concept and Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The favorable 3 : 3 stoichiometric relation of suitable functions in Cy 3 PBH 2 SiMe 3 on the one hand, and in reagents of the type [(LAu) 3 O] + on the other hand, appeared to offer the right conditions for the envisaged metathesis. It should be noted that similar effects have now been demonstrated for carbene-boranes [1].…”
Section: Concept and Resultssupporting
confidence: 70%
“…As summarized in a recent publication [1], within only a short period there have been various successful synthetic approaches to generate compounds with boride centers in various coordination environments [2 -4]. Reflecting the general movement in ligand chemistry from tertiary phosphines to carbenes, most of the newly designed systems are based on the latter, which proved to be more variable and more efficient in stabilizing boride functions.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In reports related to this work, the groups of Finze and Bertrand showed that multiple electron-withdrawing cyano substituents at anionic or neutral hydroboron species cause aB ÀHb ond umpolung, which enables deprotonation to dianion VII [14] or the cAACstabilized boryl anion VIII. [15] Inspired by these results we surmised that as ingle cyano group may suffice to induce aB ÀHb ond umpolung in [(cAAC)BH 2 (CN)] [16] (1,c AAC = 1-(2,6-i Pr 2 C 6 H 3 )-3,3,5,5-tetramethylpyrrolidin-2-ylidene) and enable deprotonation. To better understand the nucleophilic nature of the boronbound hydrogens,p artial charges (NBO) were calculated on BH 3 ,[ (cAAC)BH 3 ], and 1 at the BP86/def2-SVP level (see the Supporting Information, Figure S47).…”
mentioning
confidence: 93%
“…An X-ray structure analysis of 2 revealed adimeric structure in which the boron centers are sp 2 -hybridized (S(B) = 360.0(2)8 8), and the lithium cations bridge end-on over the cyano ligands ( Figure 2, see Table S1 for selected bond lengths and angles), similarly to VII and VIII. [14,15] Both B À Cbonds in 2 (B1-C1 1.447(3), B1-C21 1.529(3) )are significantly shorter than in the dicyanoboryl anion VIII (1.473(2) and 1.553(2) ,r espectively), [15] pointing to ah igher degree of p-backdonation from the formally anionic boron center to the cyano and cAACligands in 2 than in VIII.P lots of the frontier molecular orbitals (Table S1). [15] Compound 2 also reacted as at ypical boron nucleophile with ar ange of soft, heavier triorganotetrelchlorides,C lER 3 (R = Me,E = Sn;R = Ph, E = Ge,S n, Pb), yielding the corresponding colorless boranes,[(cAAC)BH(CN)(ER 3 )] (4-6;Scheme 1c).…”
mentioning
confidence: 99%
See 1 more Smart Citation